The determinants and effects of work-related training in Britain - Richard Blundell; Lorraine Dearden; Costas Meghir (Institute for Fiscal Studies (IFS), 1996)
Work Related training is currently at the top of the political and public policy agenda. The report looks at who gets work related training in Britain, the effect it has on the subsequent employment prospects of men and women, the wage payoffs to different types of work related training, and whether it improves the wages prospects of relatively low skilled individuals.
Keywords: 330